Struggle for energy resources in Central Asia (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Today it can be seen that global competition increases and interdependence of countries and regions became less stable. The search for an effective answer to the traditional and new challenges of international stability and security in the modern century has a huge influence on the importance of energy resources. Energy resources play a serious role for improving the quality of life and expanding opportunities for all states. Thus provision of effective, reliable and ecological secure energy supply according to the prices of fundamental marketable economy principles considered to be one of the most important challenges for the world community. Due to economic crisis the importance of Central Asian energy resources dramatically increased in the world. There are a lot of big players like Russia, China, the USA and European states which are still interested in Central Asia, weaving new strategies. So, confrontations between above-mentioned powers around Central Asian energy resources potential still exist and become more extensive.